HUBUNGAN ANTARA MINDFULNESS IBU & KONFLIK IBU DENGAN ANAK REMAJA USIA 13-15 TAHUN - Daniel Saputra; Theresia Indira Shanti (MANASA, 2019)
Mothers are expected to have good relationships with their adolescents. However, there aremany conflicts between mothers and their adolescents, which cannot be resolved properly bymothers. Therefore, mothers who have early adolescent child need to have a mindful attitudeto avoid conflicts and resolve conflicts that occur with teenagers. The aim of this study is tofind out the relationship between mindfulness and conflict among mothers who haveadolescents aged 13-15 years. Participants in this study were 118 mothers who haveadolescents aged 13-15 years, which were collected using 15-item Five Facet MindfulnessQuestionnaire (FFMQ-15) and Konflik Ibu-Anak (KIA) and convenience sampling method.Correlation analysis show that there is a significant negative relationship between mindfulnessand conflict among mothers who have adolescents aged 13-15 years (r(117) = -0.272; p <0.05,one-tailed). This finding confirmed previous study, that the mor mindfulness the mother is, themore mother aware and process her emotion, and the less conflict they she has with herdaughter. It is recommended that further analysis needed to the context of respondents.